Green Accounting dan Biaya Lingkungan: Studi Kasus pada Perusahaan Perkebunan Hanna Sejahtera Riau - Steviani Jaeni Kendek Allo (Ikatan Da'i Indonesia, 2025)
Green accounting is an accounting instrument that emphasizes the recording, measurement, and reporting of environmental costs as a form of corporate responsibility for sustainability. This study aims to analyze the implementation of green accounting at the Hanna Sejahtera Plantation Company in Riau. The research method used a qualitative descriptive approach, with data obtained through interviews and documentation. The results indicate that the company has not yet formally implemented green accounting because there is no specific recording of environmental costs. However, two categories of environmentally related costs were identified: replanting/heavy equipment costs, which are classified as internal failure costs, and road maintenance costs, which are considered preventative costs. The cost composition indicates that the company's expenditures are more reactive than preventative in response to environmental impacts. This finding indicates the need for a more structured green accounting system to improve the effectiveness of environmental management while supporting business sustainability.